Eclipse of Empires : World History in Nineteenth-Century U.S. Literature and Culture - Roylance, Patricia Jane (Book collections on Project MUSE., 2013)
This book analyzes the nineteenth-century American fascination with what the author calls "narratives of imperial eclipse," texts that depict the surpassing of one great civilization by another. The central claim in this book is that historical episodes of imperial eclipse - for example, Incan Peru yielding to Spain, or the Ojibway to the French - heightened the concerns of many American writers about specific intranational social problems plaguing the nation at the time: race, class, gender, religion, and economics.